2010
DOI: 10.1111/j.1744-7429.2010.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Patterns of Tropical Dry Forest Trees Along a Mesoscale Water Availability Gradient

Abstract: Tropical dry forests (TDFs) host a large diversity of tree species but little is known of potential mechanisms that contribute to its maintenance. Given the paramount importance of water availability in such forests, tree species would be expected to show nonrandom patterns along water availability gradients, as well as differential individual species responses. In this work we explored whether that was true for 50 dominant tree species. Within a total area of 5.2 ha, divided into 26 transects each with ten 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 61 publications
(88 reference statements)
3
45
1
6
Order By: Relevance
“…As with mature sites, we cannot assess the relative influence of other biophysical factors on biomass accumulation due to the limitations of our dataset. However, the patterns of biomass accumulation that we document in combination with evidence from studies on physiology of SDTF tree species (Balvanera et al, 2011;Singh and Kushwaha, 2005;Segura et al, 2003), support the hypothesis that MAP limits the maximum attainable biomass and possibly the rate of biomass accumulation as well. Disturbance history, including the extent to which trees were removed, post-disturbance management, the introduction of exotic species, and the proximity of intact forest or regeneration sources all are factors likely to impact the regeneration rate and the amount of biomass attained by secondary forests (Griscom and Ashton, 2011).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As with mature sites, we cannot assess the relative influence of other biophysical factors on biomass accumulation due to the limitations of our dataset. However, the patterns of biomass accumulation that we document in combination with evidence from studies on physiology of SDTF tree species (Balvanera et al, 2011;Singh and Kushwaha, 2005;Segura et al, 2003), support the hypothesis that MAP limits the maximum attainable biomass and possibly the rate of biomass accumulation as well. Disturbance history, including the extent to which trees were removed, post-disturbance management, the introduction of exotic species, and the proximity of intact forest or regeneration sources all are factors likely to impact the regeneration rate and the amount of biomass attained by secondary forests (Griscom and Ashton, 2011).…”
Section: Discussionsupporting
confidence: 76%
“…Many tree species in SDTF are distributed according to water availability (Balvanera et al, 2011), and lower rainfall sites have a greater proportion of deciduous trees (Singh and Kushwaha, 2005). By playing a role in bud break and leaf abscission, water availability limits the start and end of the growing period of deciduous trees (Borchert, 1994;Reich and Borchert, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Balvanera et al. (), in testing the effect of water‐availability gradients on tree distributions in a Mexican SDTF, have suggested that SDTFs may have a greater degree of habitat‐niche specialization compared to wetter forests. While is clear that both soils and topography exert considerable influence on local‐scale plant distributions in SDTFs, by our reading of the literature (Appendix ), the variation in the proportion of habitat specialists in a community within either forest type (tropical rainforest, SDTF) exceeds the variation across forest types.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly we propose abiotic variation within plots of old‐growth forest could lead to the observed filtering of trait values. Many species in this study display strong habitat preferences within the Reserve, related to topography and water availability (Balvanera, Quijas & Pérez‐Jiménez ). Species tracking of preferred conditions may explain the reduced range of traits compared to a random community in old‐growth forests.…”
Section: Discussionmentioning
confidence: 99%
“…). However, assembly of dry forest communities may relate to distinct or additional resources; water in particular is an important determinant of species distributions in undisturbed dry forests (Balvanera, Quijas & Pérez‐Jiménez ).…”
Section: Introductionmentioning
confidence: 99%